Depiction of Folklore and Voodoo in Zora Neale Hurston‟s Novel Jonah‟s Gourd Vine: Exploring African-American Folk Culture in Zora Neale Hurston's Jonah's Gourd Vine (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Zora Neale Hurston (1891–1961) devoted much of her career to present African-American folkculture. She presented readers a broad understanding of a highly metaphorical folk vernacular andintroduced them to hoodoo, folktales, lying competitions, spirituals, the blues, sermons, children'sgames, riddles, and playing the dozens. The purpose of this research paper is to depict some aspects offolklore in Jonah‟s Gourd Vine. Hurston's use of southern folklore lends the novel an accurate depictionof southern culture in Florida in the early 20th century. The reader gains a deeper grasp of the persons,society, and culture through her depictions of folk belief, music, and sayings. Hurston employs foursignificant forms of folk culture in Jonah's Gourd Vine folk tale, music, sayings, and belief.